Simulating capital income taxation and welfare under a DSGE framework - Unal, Umut (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This paper develops a dynamic stochastic general equilibrium (DSGE) model for analyzing the impact of various capital income tax policies in a small open economy populated by households possessing endogenous time preferences. We contribute to the literature by studying the impacts of: 1) anticipated tax shocks under stochastically growing output, 2) stochastic tax shocks under deterministic output, on our dynamic general equilibrium framework. With our model’s specifications, this is the first attempt to integrate uncertainty into the study of taxation and welfare. Our results suggest that only under certain conditions welfare paradoxes may exist, in the sense that increases in tax instruments may improve welfare. Keywords: endogenous time preference, adjustment costs, perturbation methods, stochasticshocks
Argumenta Oeconomica, 2018, Nr 1 (40), s. 81-114
Keywords: endogenous time preference; adjustment costs; perturbation methods; stochastic shocks